2020
DOI: 10.3390/f11080876
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Exploration of Perception and Use of Cultural Ecosystem Services from Tree-Based Urban Green Space in the City of Zagreb (Croatia)

Abstract: Background and Objectives: Cultural ecosystem services of urban green spaces are increasingly important and often recognized as such by people living in urban areas. Qualitative studies on perception of cultural ecosystem services from urban green spaces are still rare. Previous studies addressed only certain types of urban green space and often only some services. There is a lack of understanding how people perceive cultural ecosystem services from different types of tree-based urban green spaces. Hence, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Recreation is often an underlying motivation for interaction with urban green spaces (Krajter Ostoić et al 2020a). Walking is universally the most common recreational activity in forests (Roovers et al 2002, Arnberger 2006, Gerstenberg et al 2020, Krajter Ostoić et al 2020a, Šodková et al 2020. Visiting Forest Park Grmoščica to spend quality family time was a priority activity for most respondents (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recreation is often an underlying motivation for interaction with urban green spaces (Krajter Ostoić et al 2020a). Walking is universally the most common recreational activity in forests (Roovers et al 2002, Arnberger 2006, Gerstenberg et al 2020, Krajter Ostoić et al 2020a, Šodková et al 2020. Visiting Forest Park Grmoščica to spend quality family time was a priority activity for most respondents (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In Zagreb, qualitative research on the sample of citizens shows that they perceive various types of tree-based urban green space, especially forests and forest parks, as holders of different cultural ecosystem services, including recreation (Krajter Ostoić et al 2020a). The same research shows that forests provide more recreational opportunities than other types of urban green space, meaning that people reported more recreational activities they undertake in them.…”
mentioning
confidence: 99%
“…Residents of urban areas often recognize the cumulative cultural environmental benefits that urban green spaces offer (Ostoić et al, 2020), but their perception and understanding of UGSs is more difficult to pinpoint. Studies from a range of countries on the perception of UGSs have identified several dominant factors that influence public perceptions (Tian et al, 2020).…”
Section: Socio-demographic and Economic Factors Influencing The Perceptions Of Ugssmentioning
confidence: 99%
“…Francis et al (2012) similarly found that both the quality of parks and the users' proximity to parks were significant to the development of a sense of community. In their study in the Croatian city of Zagreb, Ostoić et al (2020) found that the perceived qualities of UGSs, such as cultural ecosystem services (Sen and Guchhait, 2021) influenced the use of these spaces. Moreover, they found that positive memories of past (for example, childhood) experiences in natural environments, their perception of urban spaces in terms of beneficial aspects of UGSs (e.g., recreational facilities) and their emotional responses to nature are essential factors needed to support urban greening.…”
Section: Urban Green Spaces and Social Cohesionmentioning
confidence: 99%
See 1 more Smart Citation